A modeling methodology to predict the generation of wasted plastic pesticide containers: An application to Greece. (15th July 2021) - Garbounis, Georgios; Komilis, Dimitrios
Abstract: Plant protection products (pesticides) are used throughout the world in the form of various types, such as insecticides, fungicides, herbicides etc. High Density Polyethylene is the principal material that those containers are made of. The aim of the study was to determine the factors that statistically affect the generation of the resulting wasted plastic pesticide containers after pesticide application. The objective was to develop a mathematical model to describe the generation rate of wasted plastic pesticide containers as a function of certain parameters. 603 data series were recorded based on information from 106 farmers in Greece and nineteen (19) parameters were initially included as potential predictors. Each farmer filled up questionnaires and provided data for more than one type of crops. Data were obtained from six Greek prefectures. Empirical models were developed for all pesticides through linear regression. The cultivated area (m 2 ), the type of crop (perennial/annual, irrigated/dry) and the type of pesticide application (on soil, on foliage) were the statistically significant parameters to affect generation rates. Eighteen (18) farmers provided 56 (new) observations to validate the models. Two of the four models are reliable due to their low validation errors and should be ideally used for crop areas above 58, 000 m 2 . The total wasted plastic pesticide containers generation rate in Greece was estimated to be 0.028 kg farmer −1 y −1 1000 m −2 . Modeling results can aid to predict the generation rate of wasted pesticide plastic containers at a regional and national level so that to properly design their management systems.